Centro de investigación y capacitación en construcción sostenible - Plan parcial parque de desarrollo social eje integrador regional sur (Soacha – Girardot) (2018)
The proposal of the research and training center in sustainable construction sale of several of the different issues and the sustainability of the sector, seeks the recovery and recovery of the environment, economy and land use. On the other hand, the equipment seeks to improve different problems, but also means a better use of services provided in an adequate and optimal way.